Nonhomologous end joining: new accessory factors fine tune the machinery. Issue 6 (June 2021) - Ghosh, Dipayan; Raghavan, Sathees C.
Abstract : Nonhomologous DNA end joining (NHEJ) is one of the major DNA double-strand break (DSB) repair pathways in eukaryotes. The well-known critical proteins involved in NHEJ include Ku70/80, DNA-PKcs, Artemis, DNA pol λ/μ, DNA ligase IV–XRCC4, and XLF. Recent studies have added a number of new proteins to the NHEJ repertoire namely paralog of XRCC4 and XLF (PAXX), modulator of retroviral infection (MRI)/ cell cycle regulator of NHEJ (CYREN), transactivation response DNA-binding protein (TARDBP) of 43 kDa (TDP-43), intermediate filament family orphan (IFFO1), ERCC excision repair 6 like 2 (ERCC6L2), and RNase H2. PAXX acts as a stabilizing factor for the main NHEJ components. MRI/CYREN seems to play a dual role stimulating NHEJ in the G1 phase of the cell cycle, while inhibiting the pathway in the S and G2 phases. TDP-43 can recruit the ligase IV–XRCC4 complex to the DSB sites and stimulate ligation in neuronal cells. RNase H2 excises out the ribonucleotides inserted during repair by DNA polymerase μ/TdT. This review provides a brief glimpse into how these new partners were discovered and their contribution to the mechanism and regulation of NHEJ. Highlights: NHEJ is one of the major DNA DSB repair pathways in humans. During NHEJ, Ku heterodimer consisting of KU70/80 binds to DSBs, followed by end processing by nucleases, gap filling by error-prone DNA polymerases, and finally ligation of the nick performed by DNA ligase IV–XRCC4 complex. PAXX and MRI are two important recently identified proteins associated with NHEJ. Novel and important functions in NHEJ have been attributed to the already known proteins, TDP-43, FOXL2, and RNase H2. Discovery of new factors provide additional insights into the mechanism and regulation of NHEJ, and its potential use in targeted therapy in human pathologies.